Effect of Control Delay in AMC in Asymmetric TDD Systems - Lynn, N.; Takyu, O.; Nakagawa, M.; Esmailzadeh, R. (2006 IEEE Singapore International Conference on Communication Systems : Singapore, 30 October - 2 November 2006, 2006)
This paper evaluates downlink throughput performance affected by asymmetric slot allocation in time division duplex (TDD) systems that employ adaptive modulation and coding (AMC). By exploiting channel reciprocity TDD systems can utilize open loop channel estimation to adaptively change modulation and coding scheme (MCS) in AMC. However, control delay in AMC in asymmetric TDD systems is subject to time slot allocation formats. Large control delay in AMC leads to the selection of an inappropriate MCS. We present an analytical approach to calculate the probability of MCS level selection error in different channel conditions for different asymmetric time slot allocations. The results of numerical calculation are validated by the simulated results. Finally throughput performance affected by different TDD asymmetric formats is discussed based on respective MCS false selection probability in each time slot allocation format